Information Policy of the Enterprise as a Factor of Ensuring Competitiveness - AKHMETSHIN, Elvir M.; TOLMACHEV, Alexey V.; NIKOLAEVA, Tatiana E.; ANDRYUSHCHENKO, Iryna Ye. (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
In this research, we determined that the development of objects of entrepreneurial activity can take place only on condition of equal access to external and internal resources of development. Access to resources, as well as increasing work competitiveness, is defined as the possibility of forming an enterprise environment and its independent actions. The basis of such an environment is the formation of an information-type policy that allows fully determining the opportunities for attracting development resources, as well as improving the financial stability of the enterprise in the external market. The subject of the study is the process of the information policy of the enterprise formation, as well as the factors of its formation as a separate formative value for determining whether the enterprise is competitive. The novelty of the research is the process of formation and presentation in the various information and social and economic processes of the enterprise’s information policy. The direction of further research is the integrative functions of ensuring the development of accounting and transformation of information policy into the enterprise’s capital.